Role of intermittent self catheterization in prevention of recurrence of stricture urethra following visual internal urethrotomy: a prospective single centre study - Kumar R., Vijaya; Dharwadkar, Sachin; Doshi, Chirag; Batta, Akshey (International Surgery Journal, 2019)
Background: Stricture urethra is a highly recurrent disease. Various treatment modalities were used to prevent its recurrence post urethrotomy with variable success. The objective of this randomized study was to compare the stricture recurrence after optical internal urethrotomy with and without clean intermittent self catheterization in patients with anterior urethral stricture. Methods: A total of fourty patients aging 20-60 years with urethral stricture of up to 1cm and up to six months duration were selected randomly in to treatment group A (20 patients) control group B (20patients) and all patients were treated with VIU followed with indwelling catheter for 7 days. Patients with traumatic urethral stricture, congenital or malignant strictures were excluded. The treatment group A was taught to perform self clean intermittent catheterization by inserting Nelaton catheter. All patients were followed regularly at 3,6,12 months. Results: 4 (20%) patients in treatment group A had stricture recurrence while 15 (75%) out of 20 patients in control group B developed urethral stricture recurrence. In Group A 2 Patient developed stricture in first 6 months and 2 in next 6 months of follow up while in control group B 10 patients (50%)out of 20 had their recurrence in the first six months of follow-up while 5 (25%) in group B had their recurrence in the next six months of follow-up. Conclusions: Clean self intermittent catheterization is a simple, safe, cost effective and easy to perform procedure for prevention of urethral stricture with good acceptability and compliance.